Implementasi E-Purchasing pada Proses Pengadaan Barang dan Jasa Secara Elektronik di Kecamatan Tebet Jakarta Selatan - Lenggogeni Amelia Puti Chaidir; Elisa Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivated by indications of problems in the e-purchasing process, such as delays in creating packages in the e-catalogue application, and Goods and Services Procurement Officials (PP) facing difficulties finding items with the types or models that meets the expected specifications due to the limited variety of catalogs in the application. This research aims to understand the implementation of e-purchasing in the process of electronic procurement of goods and services in Tebet District. The research method used in this research is qualitative research with a descriptive approach using data collection techniques through interviews, observation and documentation. To determine the right informants who are experts in their field, this research used a purposive sampling technique. The data analysis techniques used are data reduction, data presentation, drawing conclusions and verification. The analyzed data is then checked for validity using triangulation techniques. The results of the research show that Tebet District has implemented the process of procuring goods and services through e-purchasing in accordance with the theory of the process of procuring goods and services by Siahaya (2016). However, differences were observed in the process of determining the Self-Estimated Price (HPS) and the determination of the type and method of offering.